Students' perceptions towards assignment integration between architecture design studio and structural and technological subjects / Ruzanah Abu Bakar ... [et.al.] - Abu Bakar, Ruzanah; Zaini, Atta Idrawani; Kamaruddin, Siti Syariazulfa; Raja Mohd Yazi, Raja Nur Syaheeza (2023)
Architecture is a process of planning, designing, and constructing buildings or structures. In architecture, structural and technological aspects need to be considered in the design process for better service. Architecture Design Studio (ADS) is the fundamental course of the Architecture Programme. It teaches students about the design process and techniques via design projects. Courses on structure and technology (S&T), on the other hand, teach students technical knowledge. In the evolution of the University Malaysia Sarawak (UNIMAS) architecture programme, these two - ADS and S&T - are integrated to enhance critical thinking and design ability. Integration is achieved by requiring students to apply the knowledge that they have gained in S&T courses to their design projects in ADS. This study investigated the perception of students towards this integration.